2018
DOI: 10.2337/db18-0417
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Causes Mitochondrial Dysfunction as a Result of Impaired ADP Sensitivity

Abstract: Although molecular approaches altering mitochondrial content have implied a direct relationship between mitochondrial bioenergetics and insulin sensitivity, paradoxically, consumption of a high-fat (HF) diet increases mitochondrial content while inducing insulin resistance. We hypothesized that despite the induction of mitochondrial biogenesis, consumption of an HF diet would impair mitochondrial ADP sensitivity in skeletal muscle of mice and therefore manifest in mitochondrial dysfunction in the presence of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 25 publications
6
95
3
Order By: Relevance
“…If anything, there was a marginal trend for improved ADP sensitivity following immobilization in the control group using 2 independent experiments (i.e., apparent Km and the ability for ADP to suppress ROS rates), which we postulate is a potential compensatory response in an attempt to maintain energy homeostasis in the presence of reduced mitochondrial capacity that was not required following v-3 supplementation. In contrast to other models that exhibit reductions in ADP sensitivity (21,22), the lower VDAC/ANT proteins in addition to mitochondrial subunits following 2 wk of immobilization may require an increased affinity for ADP in order to maintain energy homeostasis. This could be related to the drastic nature of muscle disuse as opposed to prolonged stressors such as aging (21), the development of diabetes (32), and high dietary fat consumption (22).…”
Section: Immobilization and Mitochondrial Adp Sensitivitymentioning
confidence: 64%
See 3 more Smart Citations
“…If anything, there was a marginal trend for improved ADP sensitivity following immobilization in the control group using 2 independent experiments (i.e., apparent Km and the ability for ADP to suppress ROS rates), which we postulate is a potential compensatory response in an attempt to maintain energy homeostasis in the presence of reduced mitochondrial capacity that was not required following v-3 supplementation. In contrast to other models that exhibit reductions in ADP sensitivity (21,22), the lower VDAC/ANT proteins in addition to mitochondrial subunits following 2 wk of immobilization may require an increased affinity for ADP in order to maintain energy homeostasis. This could be related to the drastic nature of muscle disuse as opposed to prolonged stressors such as aging (21), the development of diabetes (32), and high dietary fat consumption (22).…”
Section: Immobilization and Mitochondrial Adp Sensitivitymentioning
confidence: 64%
“…In contrast to other models that exhibit reductions in ADP sensitivity (21,22), the lower VDAC/ANT proteins in addition to mitochondrial subunits following 2 wk of immobilization may require an increased affinity for ADP in order to maintain energy homeostasis. This could be related to the drastic nature of muscle disuse as opposed to prolonged stressors such as aging (21), the development of diabetes (32), and high dietary fat consumption (22). Together, these data further support the ability for mitochondria to adapt in terms of ADP responsiveness in the presence or absence of a reduction in mitochondrial capacity while highlighting the practical importance of v-3 supplementation prior to and during short periods of muscle disuse.…”
Section: Immobilization and Mitochondrial Adp Sensitivitymentioning
confidence: 64%
See 2 more Smart Citations
“…Therefore, other mechanisms might be playing important roles and affecting the results obtained here. Also, it is important to note that Miotto, LeBlanc & Holloway (2018) showed, in red gastrocnemius, a reduction in ADP sensitivity after 28 days of HFD in C57/BlJ6 mice, suggesting that muscles with different fibre-type compositions could respond in different ways to lipid overload. Phielix et al (2014) demonstrated insulin resistance at the mitochondrial level by showing that obese insulin-resistant and T2DM patients were not able to increase O 2 flux after insulin stimulation.…”
Section: Discussionmentioning
confidence: 99%